南极磷虾油不同极性脂质的提取工艺优化Optimization of extraction process of different polar lipids in Antarctic krill oil - 罗静茹，杨云云，王太伟，谢亮亮，朱西平，朱秀灵， 张瑞涛，张恒，郭玉宝，谢丹 LUO Jingru，YANG Yunyun，WANG Taiwei，XIE Liangliang，ZHU Xiping， ZHU Xiuling，ZHANG Ruitao，ZHANG Heng，GUO Yubao，XIE Dan (Zhongguo youzhi)
旨在为南极磷虾油的开发利用提供参考，以南极磷虾粉为试验材料，首先采用超临界CO2萃取中性脂质，再以乙醇提取极性脂质，通过单因素试验与响应面试验优化南极磷虾油不同极性脂质的提取工艺，并对两种脂质的组分进行测定。结果表明：超临界CO2萃取中性脂质的最佳工艺条件为萃取压力45 MPa、萃取温度45 ℃、萃取时间1.75 h，在此条件下中性脂质中甘油三酯含量为7368%，虾青素、生育酚和维生素A含量分别为74.91、44.96、448.31 mg/kg，脂质提取率为4081%;乙醇提取极性脂质的最佳工艺条件为料液比1∶ 3、提取温度57 ℃、提取时间3 h，在此条件下极性脂质中磷脂含量为80.19%，EPA和DHA含量分别为20.74%和11.43%，脂质提取率为58.37%。综上，采用超临界CO2萃取和乙醇提取相结合的方法可有效分离南极磷虾油中性脂质与极性脂质。 In order to provide a reference for the development and utilization of Antarctic krill oil, with Antarctic krill powder as material, the neutral lipids were extracted by supercritical CO2 and then polar lipids were extracted by ethanol. The extraction process of different polar lipids in Antarctic krill oil were optimized by single factor experiment and response surface methodology, and the components of the two lipids were determined. The results showed that the optimal extraction conditions of neutral lipids by the combination of supercritical CO2 were extraction pressure 45 MPa, extraction temperature 45 ℃ and extraction time 1.75 h. Under these conditions, the content of triglyceride in neutral lipids was 73.68%, the contents of astaxanthin, tocopherol and vitamin A were 74.91, 44.96 mg/kg and 448.31 mg/kg, respectively, and the extraction rate of lipids was 40.81%. The optimal extraction conditions of polar lipids by ethanol were solid-liquid ratio 1∶ 3, extraction temperature 57 ℃ and extraction time 3 h. Under these conditions, the content of phospholipid in polar lipids was 80.19%, the contents of EPA and DHA were 20.74% and 11.43%, respectively, and the extraction rate of lipids was 58.37%.In conclusion, the combination of supercritical CO2 extraction and ethanol extraction can effectively separate neutral lipids and polar lipids in Antarctic krill oil.